EKSISTENSI HILAL DI SIANG HARI DALAM PENENTUAN AWAL BULAN HIJRIAH MENURUT PANDANGAN MUHAMMADIYAH - Nabila, Al Ainun; Irfan, Irfan (HISABUNA: Jurnal Ilmu Falak, 2025)
ABSTRACT This study examines Muhammadiyah's view on determining the beginning of the Hijri month in the context of the phenomenon of the crescent moon appearing astronomically during the day. The main focus of this study is directed at the concept of determining the beginning of the Hijri month according to Muhammadiyah's view on the existence of the crescent moon during the day and astronomical analysis of the phenomenon of the appearance of the crescent moon before sunset. This study uses a qualitative approach with literature study and interview methods as data collection techniques. Data are analyzed descriptively-analystically with a normative-astronomical approach. The results of the study show that Muhammadiyah holds the principle that the beginning of the Hijri month is determined based on the existence of the crescent moon above the horizon at sunset, not merely its astronomical existence during the day. From the perspective of Islamic astronomy, the phenomenon of the crescent moon during the day can be explained scientifically as a post-conjunction phase, but does not yet meet the sharia requirements for determining the beginning of the month. The implications of the study show the importance of integration between science and sharia in the renewal of astronomical thinking and the need for constructive dialogue between the hisab and rukyat methods in order to achieve the unity of the Islamic calendar.